SOCIAL WORK – HELP FOR PEOPLE WITH DISABILITIES – A POLISH PERSPECTIVE. EDUCATIONAL OPPORTUNITIES FOR PEOPLE WITH DISABILITIES IN POLAND - Skoczyńska-Prokopowicz, Barbara (Uniwersyteckie Czasopismo Socjologiczne, 2016)
The author describes the working of the education system in Poland with special emphasis on pupils with disabilities. This paper pays special attention to positive changes in the perception of people with disabilities and the positive impact this has had on the legislative system in Poland, which has influenced every level of education. The author describes one very significant example where such changes are already bringing great improvement, at Rzeszow University. Even though it is one of the poorest regions in Poland, it has the highest number of students per 1000 inhabitants.